Analisis Kinerja Keuangan dengan Model Altman Z-Score pada PT Wijaya Karya (Persero) - Fadhil Hafizh Nabil; Sabrina Faylesia; Cindy Fasabillah Putri (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
Financial health evaluation of a company is one of the most crucial actions to predict the possibility of bankruptcy, especially for companies in the construction sector, such as PT Wijaya Karya (Persero) TBK. This study aims to analyze the company's financial performance using the Altman Z-Score model (https://www.idx.co.id/). It reflects a device with unpredictable capacity according to financial conditions. This model integrates five main indicators: operating capital and total assets, relative profit of total assets, tax based on earnings before interest and total assets, stock market value, and total asset sales. This study utilizes the annual financial report of PT Wijaya Karya for a certain period and quantitative analysis of z-score values ​​is carried out annually. The calculation results show variations in z scores. This indicates that the company's financial condition is in several periods of less strong zones (gray areas). In other words, the company is in a very vulnerable state due to potential financial problems. This finding indicates how crucial it is to conduct a comprehensive evaluation of the company's financial structure and strengthen its financial management tactics. The Altman Z-Score model has proven effective as an early identification tool to assess bankruptcy risk and support decision-making by management, investors, and other stakeholders.